2020
DOI: 10.1177/0146167220959176
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Laws on Norms Perceptions

Abstract: When opinions in a society change toward more or less tolerance of a group, people do not necessarily see it. Drawing on a quasi-representative survey (Study 1, N = 830) and a natural experiment (Study 2, N = 437), we investigated people’s perceptions of the societal norms toward sexual minorities and the influence of laws on these (mis-)perceptions. Study 1 indicated pluralistic ignorance as participants overestimated the societal disapproval toward same-sex issues. Complementing this finding, Study 2 found t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 45 publications
(69 reference statements)
1
33
1
Order By: Relevance
“…The political system in which people live affects people's behavior (Ayanian & Tausch, 2016;Odağ et al, 2016). Furthermore, institutional policies are a strong signal of the direction in which a society is heading (Eisner et al, 2020;Tankard & Paluck, 2016). Thus, it seems plausible that more democratic political systems, with liberal and progressive orientations and more integrative policies, should strengthen the impact of intergroup contact on advantaged group members' support for social change toward greater social equality.…”
Section: The Road Ahead-suggestions For a Comprehensive Research Agenmentioning
confidence: 99%
“…The political system in which people live affects people's behavior (Ayanian & Tausch, 2016;Odağ et al, 2016). Furthermore, institutional policies are a strong signal of the direction in which a society is heading (Eisner et al, 2020;Tankard & Paluck, 2016). Thus, it seems plausible that more democratic political systems, with liberal and progressive orientations and more integrative policies, should strengthen the impact of intergroup contact on advantaged group members' support for social change toward greater social equality.…”
Section: The Road Ahead-suggestions For a Comprehensive Research Agenmentioning
confidence: 99%
“…Recent research shows that perceived discrimination and toleration among LGBTQ+ people in Turkey undermines their wellbeing through threatening their identity needs such as self-esteem, belonging, and meaning (Bagci et al, 2020). Moreover, people tend to overestimate the rejection regarding their identities by society (Eisner et al, 2020). However, as our study showed, even a simple reminder of societal acceptance can be useful in helping people reduce the conflict between their incompatible identities.…”
Section: Discussionmentioning
confidence: 57%
“…However, data from the World Value Survey shows that societal acceptance of homosexuality has been steadily increasing across the world even though it is slower in Muslim countries (Anderson et al, 2021). However, there is a high prevalence of pluralistic ignorance regarding same-sex issues such that people overestimate the societal disapproval of homosexuality (Eisner et al, 2020). Therefore, gay communities should be reminded that the societal acceptance is increasing, and the consequences of this acceptance should be investigated.…”
Section: The Context Of the Current Studymentioning
confidence: 99%
“…However, the two concepts can be differentiated. Expressive suppression involves inhibiting the overt display of emotions (Gross & Levenson, 1993 ), whereas collective action depends upon group identification, perceptions of injustice, and shared behaviors aimed at supporting or challenging the social system (Becker, 2012 ; Turner-Zwinkels & van Zomeren, 2020 ). Thus, expressive suppression targets the expression of emotions, whereas support for collective action focuses on behavior.…”
Section: Studymentioning
confidence: 99%